Representations of the Outsider in David Bowie’s Glam Period and its Continuation Through Punk, Goth, and Emo: Thematic, Aesthetic, and Subcultural Considerations - Hall, Nerhys (Université d'Ottawa / University of Ottawa, 2015)
Popular music artists portray a variety of themes through the aesthetics of their music, lyrics, and music videos. One theme in particular that began with David Bowie’s glam period (1972-1974) and the creation of his Ziggy Stardust persona is the notion of the Outsider. Bowie not only portrayed an Outsider character, but also spoke to and for those who felt like Outsiders. Punk, goth, and emo bands that were influenced by Bowie took this social stance to speak to and for their own versions of the Outsider. Drawing from subcultural theory, music analysis, and music video analysis, and using Bowie as a benchmark and influence, I explore how several other bands portray the Outsider in their music, lyrics, and music videos.
Keywords: Music; Popular Music; Subcultures; Aesthetics; Themes; Outsider